Answers

  • Brainly User
2016-03-06T22:48:41+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Two consecutive integers: x, (x+1)
Reciprocals = 1/x , 1/(x+1)

Sum of reciprocals = 11/30
   1/x  + 1/(x+1)       = 11/30

Multiply equation by 30x(x+1) and you have:
= 30x + 30(x+1) = 11x(x+1)
= 30x + 30x+30 = 11x^2 + 11x
= 60x+30           = 11x^2+11x
                       0 = 11x^2+11x-60x-30

So, this is a quadratic equation. We can simplify the expression further.
11x^2+11x-60x-30 = 0
11x^2 - 49x - 30     = 0

Now, the factors of the expression are :
=(11x + 6)((x - 5) = 0

In (x-5), we can say 5 is the integral solution and therefore,
x = 5

So, the first number is 5
The second number = x+1   = 5+1
                                             = 6

The two numbers = 5,6
1 5 1
Comment has been deleted
Comment has been deleted
Comment has been deleted
The Brainliest Answer!
2016-03-06T22:50:43+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let The Number be x and x + 1
According To Given Statement
1  +     1       = 11
---     ------       -----
x       x + 1       30
x + 1 + x   = 11
------------    ------
  x² + x         30
60x + 30 = 11x² + 11x
11x² + 11x - 60x - 30  = 0
11x² - 49x- 30  = 0
11x² - 55x + 6x - 30 = 0
11x(x - 5) +6(x - 5) = 0
(11x + 6)(x - 5) = 0
x = -6/11 OR x = 5

Therefore the first No . is 5 as -6/11 is Not a Natural No.
So ,
Second Natural No = 6

So the Numbers are 5 and 6

Mark This Brainliest If This Was Helpful

3 4 3